Some characteristics of drifting snow at Mizuho Station, East Antarctica, 1982 - Takahashi, Shuhei; Ohmae, Hirokazu; Ishikawa, Masao; Katsushima, Takayoshi; Nishio, Fumihiko (1984)
P(論文) Several measurements on drifting snow were carried out at Mizuho Station (70°42′S, 44°20′E, 2230m, above sea level)) East Antarctica, in 1982. Visibility was correlated to wind velocity on a logarithmic plot; it was proportional to about the -8 power of wind velocity over a year. This is explained by the reciprocal relation of visibility to drift density and the power relation of drift density to wind velocity. Moreover, visibility changed with the seasonal variation of daylight. The repose angle of drifting snow particles was observed by measuring the inclination of a cone shape deposit formed in sub-surface chamber. The repose angle was more than 80° in the case of snow falling and less than 80° in the case of no precipitation. The angle in the case of no precipitation showed a temperature dependence. The fall velocity of drifting snow particles in still air was observed. The fall velocity was between 0.3 and 0.9m/s and depended on wind velocity and snow particle shape. This dependence is explained by the change of particle size or drag coefficient. departmental bulletin paper